Assessment of selected local plants feed intake and reproductive performance in female goats - Abdul Halim, Norhazirah (2017)
Malaysian goat production could be highly dependent on nutritional management. It is important to assess the effect of goats’ nutritional management especially feeding practices on the goat production for maximizing the reproductive efficiency of the goats. Therefore, our study was conducted with aims; 1) to assess the effect of different types of feed on the reproductive performance of female goats under intensive and semi-intensive farm systems in Peninsular Malaysia, and 2) to evaluate the effects of different pre-breeding dietary intake on reproductive performance of female goats. Goat farm surveys and experimental of animals were conducted to achieve the aims. For farm surveys, a set of questionnaires were used to acquire data on feeding practices and goat reproductive performance including abortion and kidding performances from 212 respondents who involved with goat breeding for more than a year in Peninsular Malaysia. The surveys were conducted in about 8 months from January to August 2014. While for the experimental of animals, thirty-two female goats were used and were assigned into four groups: Group 1 was given a maintenance (M) diet of Napier and Guinea grass, Group 2 was given 2M of Napier grass and commercial concentrate, Group 3 was given 2M of Napier grass and Chinese Violet and Group 4 was given 1M of Napier grass and Jackfruit leaves. The treatment diets were given daily for 10 days prior to their mating period (Day -9 until Day 0). Ovulation and pregnancy rates were determined from observation of corpora lutea and fetus scanned on Day 14 and Day 49 respectively after the mating period. Kidding and twinning rates were determined through the kidding performances. Progesterone level was determined from doe s’ blood samples taken every two or three days during the experiment. The result of the survey revealed that the kidding rate of goats were higher in farms where additional feeds were given (1.27 ± 0.06) compared to not given (1.03 ± 0.06) (p<0.05). Intake of Chinese Violet, banana leaf and silage have a significant relationship with early abortion (p<0.05) while, intakes of Napier grass and silage have a significant relationship with late abortion (p<0.05). Additional feed intakes have a significant association with early abortion (X2=11.36, p<0.05) and twin kids (X2=10.44, p<0.05). Feeding Chinese Violet, concentrate and Napier grass have significant association with twin kids (p<0.05). Meanwhile, the result of animal experimental shows that Group 2 does has highest ovulation rate (1.86 ± 0.34), pregnancy rate (57.2%), twinning rate (66.7%) and litter size (1.7) and lowest overall abortion rate (50.0%). Group 1 had highest progesterone level on Day 0, 9 and 22 (p<0.05). Overall, from present study, it showed that commercial concentrate could affect pregnancy rate, kidding rate, twinning rate and litter size of goats. In addition, this feed intake has potential as feed supplementation for female goats where it could increase the kidding rate.